The Analysis of Semantic Meaning Found in Seven Poems by Sapardi Djoko Damono - Dionisius Kasa Taek (PRAGMATICA : Journal of Linguistics and Literature, 2023)
The aim of this research is to identify the types of semantic meaning found in seven (7) poems by Sapardi Djoko Damono. The data in this research are phrases, clauses and sentences found in Sapardi Djoko Damono's poems. This research mainly discusses seven types of meaning in Semantics based on Leech's theory. The method used in this research is quantitative descriptive. The data collection method used in this research is the observation method. Based on the analysis, five types of semantic meaning were found in seven Sapardi Djoko Damono poems. Namely, conceptual meaning, connotative meaning, social meaning, affective meaning and thematic meaning. The type of meaning that is most often found is connotative meaning. Sapardi Djoko Damono writes beautifully about longing and love in his poetry. Thus, to this day his poems are still remembered.